2014
DOI: 10.1021/ac5026418
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Insights into Retention at a Reversed-Phase Chromatographic Interface

Abstract: The efficiency of chromatographic separations decreases markedly when peaks exhibit asymmetry (e.g., "peak tailing"). Theoretically, these effects can arise from heterogeneous adsorption kinetics. To investigate the nature and consequences of such heterogeneity, we used a combination of single-molecule imaging and reversed-phase liquid chromatography (RPLC). In both single-molecule and macroscopic RPLC experiments, the stationary phase was hydrophobic end-capped (trimethylsilyl-functionalized) silica, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 47 publications
4
92
0
Order By: Relevance
“…Object positions were calculated as the centroid of intensity with a localization precision of ∼50 nm. 22 Molecular trajectories were constructed by linking an object's center of intensity to the nearest center of intensity within a distance (i.e., tracking radius) of 4 pixels (1.08 μm) in subsequent frames. Protein kinetics were found to be insensitive to the tracking radius selected (see Figure S12 in the Supporting Information).…”
Section: Thin Polymer Film Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Object positions were calculated as the centroid of intensity with a localization precision of ∼50 nm. 22 Molecular trajectories were constructed by linking an object's center of intensity to the nearest center of intensity within a distance (i.e., tracking radius) of 4 pixels (1.08 μm) in subsequent frames. Protein kinetics were found to be insensitive to the tracking radius selected (see Figure S12 in the Supporting Information).…”
Section: Thin Polymer Film Preparation and Characterizationmentioning
confidence: 99%
“…By creating these maps, we were able to accurately measure adsorption and desorption kinetics for molecular-scale surface sites and, importantly, identify distinct populations of sites. The specific mapping methods were described previously by Mabry et al 22 The initial position of each molecular trajectory was placed on a pseudoimage with 22.7 nm pixels (10× smaller than camera pixels) and blurred such that an adsorption center was represented by Gaussian peak with a standard deviation σ loc and an amplitude of 1 adsorption event. Super-resolution adsorption event maps were constructed by summing all blurred pseudoimage adsorption events.…”
Section: Thin Polymer Film Preparation and Characterizationmentioning
confidence: 99%
“…28 Consistent with these previous findings, the frequency of strong adsorption (i.e., confinement) reached a minimum at 25% methanol and was correlated with specific regions of the surface. The TMS surface is known to have spatially rare, anomalously strong surface sites, 14,15 and adsorption maps showed that binding onto strong sites correlated with the frequency of confinement (Figures S-7 and S-8, Table S-3).…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…The channels were aligned and molecules identified as described previously (using an image processing routine where the raw images were convolved with a disk matrix and then thresholded to identify distinct objects). 76,83 Only molecules adsorbed to the interface were localized during image processing because diffusion in solution was too fast to allow localization at the 100 ms frame acquisition times used in these experiments. Previous studies of FS and TMS surfaces have shown that adsorbed molecules are typically confined to regions smaller than the localization precision (∼100 nm).…”
Section: Solutions Of End-labeled Peptidementioning
confidence: 99%